Rapid diagnosis of Tobacco mosaic virus in tobacco using time-resolved fluorescence immunoassay - Yuan Ji; Yushuang Guo; Huimin Deng; Jianfeng Zhang; Yuemao Wang; En Dai; Ziyan Fan; Gangling Tang; Mengao Jia; Bo Ding (Food and Agricultural Immunology, 2023)
ABSTRACTTobacco mosaic virus (TMV) causes a significant yield loss in solanaceous crops. Accurate and rapid diagnosis of TMV is an essential pre-requisite for proactive and tailored disease management strategies, filling the gap between more rigorous laws regarding pesticide use and maintaining crop production. Herein, we developed a time-resolved fluorescence immunoassay (TRFIA) to quantitatively detect TMV in tobacco. TMV virions were used as immunogens to develop monoclonal antibodies, which were then conjugated to Eu3+ nanospheres. The detection limit of the TRFIA platform was 0.24 ng/mL, with recovery rates in the range of 90.71–108.11% in spiked tobacco. The specificity was confirmed using ten species of tobacco-infecting phytopathogens. In-field applicability was implemented by screening for TMV in 10,000 tobacco leaf samples collected from five fields in Kunming, China. Overall, the proposed TRFIA platform is rapid, accurate, and end-user friendly, demonstrating its application in TMV onsite testing in tobacco.